Community needs analysis on community preparedness related to health aspect in facing flash floods disaster in afdeling Gunung Pasar Jember - Dhyani Ayu Perwiraningrum; Rahmat Hidayat; Fatwa Sari Tetra Dewi (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
PurposeThe purpose of this study was to analyze the needs of the community to improve community preparedness related to health aspects in facing flash floods disaster in afdeling Gunung Pasar, Jember.MethodA phenomenological study was conducted through focused group discussions, indepth interviews and observations of the Afdeling community, community leaders, head of village office, community stakeholders and stakeholders of disaster management (institution of local government) at Gunung Pasang Jember.ResultsThe study found that first, the community needs a preparedness drive for health preparation and area monitoring, including the provision of disaster facilities and infrastructure, training, coordination and disaster information. Second, efforts to fulfill normative need in health preparedness by stakeholders are still minimal.ConclusionStudy of social representation of community experiences in disasters, stimuli of community needs such as emergency response training, compliance tools, disaster information and coordination with stakeholders. These needs are needed as prevention efforts related to health problems and observation of dangerous zones at Afdeling Gunung Pasang. Education, counseling and emergency response training needs to be done to the community to improve community preparedness and awareness of the hazards of the disaster.